enow.com Web Search

Search results

  1. Results from the WOW.Com Content Network
  2. Binomial theorem - Wikipedia

    en.wikipedia.org/wiki/Binomial_theorem

    In elementary algebra, the binomial theorem (or binomial expansion) describes the algebraic expansion of powers of a binomial.According to the theorem, the power ⁠ (+) ⁠ expands into a polynomial with terms of the form ⁠ ⁠, where the exponents ⁠ ⁠ and ⁠ ⁠ are nonnegative integers satisfying ⁠ + = ⁠ and the coefficient ⁠ ⁠ of each term is a specific positive integer ...

  3. Binomial coefficient - Wikipedia

    en.wikipedia.org/wiki/Binomial_coefficient

    The binomial coefficients can be arranged to form Pascal's triangle, in which each entry is the sum of the two immediately above. Visualisation of binomial expansion up to the 4th power. In mathematics, the binomial coefficients are the positive integers that occur as coefficients in the binomial theorem.

  4. Binomial series - Wikipedia

    en.wikipedia.org/wiki/Binomial_series

    Differentiating term-wise the binomial series within the disk of convergence | x | < 1 and using formula , one has that the sum of the series is an analytic function solving the ordinary differential equation (1 + x)u′(x) − αu(x) = 0 with initial condition u(0) = 1. The unique solution of this problem is the function u(x) = (1 + x) α.

  5. Binomial (polynomial) - Wikipedia

    en.wikipedia.org/wiki/Binomial_(polynomial)

    The expansion of the n th power uses the numbers n rows down from the top of the triangle. An application of the above formula for the square of a binomial is the "(m, n)-formula" for generating Pythagorean triples: For m < n, let a = n 2 − m 2, b = 2mn, and c = n 2 + m 2; then a 2 + b 2 = c 2.

  6. Kummer's theorem - Wikipedia

    en.wikipedia.org/wiki/Kummer's_theorem

    To compute the largest power of 2 dividing the binomial coefficient () write m = 3 and n − m = 7 in base p = 2 as 3 = 11 2 and 7 = 111 2.Carrying out the addition 11 2 + 111 2 = 1010 2 in base 2 requires three carries:

  7. General Leibniz rule - Wikipedia

    en.wikipedia.org/wiki/General_Leibniz_rule

    The Leibniz rule bears a strong resemblance to the binomial theorem, and in fact the binomial theorem can be proven directly from the Leibniz rule by taking () = and () =, which gives ( a + b ) n e ( a + b ) x = e ( a + b ) x ∑ k = 0 n ( n k ) a n − k b k , {\displaystyle (a+b)^{n}e^{(a+b)x}=e^{(a+b)x}\sum _{k=0}^{n}{\binom {n}{k}}a^{n-k}b ...

  8. Abel's binomial theorem - Wikipedia

    en.wikipedia.org/wiki/Abel's_binomial_theorem

    1 Example. Toggle Example subsection. 1.1 The case m = 2. 2 See also. ... is a mathematical identity involving sums of binomial coefficients. It states the following:

  9. Stars and bars (combinatorics) - Wikipedia

    en.wikipedia.org/wiki/Stars_and_bars_(combinatorics)

    The solution to this particular problem is given by the binomial coefficient (+), which is the number of subsets of size k − 1 that can be formed from a set of size n + k − 1. If, for example, there are two balls and three bins, then the number of ways of placing the balls is ( 2 + 3 − 1 3 − 1 ) = ( 4 2 ) = 6 {\displaystyle {\tbinom {2 ...